Manufacture of Partially Biodegradable Composite Materials Based on PLA-Tires Powder: Process and Characterization - Carlos Rolando Rios-Soberanis; Shuchi Wakayama; Takenobo Sakai; José de los Ángeles Rodriguez-Laviada; Emilio Pérez-Pacheco (International Journal of Polymer Science)
This research work focuses on the processability and mechanical characterization of blends of polylactic acid (PLA) and tire (elastomeric part). Wasted tires used as filler in the PLA matrix were reduced by two different processes (thermal shock and pyrolysis) in order to acquire the solid residuals in powder to be characterized and compared. Elastomeric solids obtained from scraped tires were used as filler in the PLA matrix and mixed in a Brabender 60 cc mixer at different concentrations ranging from 0% to 60% of filler volume fraction. The blend was laminated, and then samples were obtained in order to undertake mechanical properties at tension and Izod impact tests. A fully detailed analysis on the solid powders by Differential Scanning Calorimeter (DSC), thermogravimetric analysis (TGA), infrared analysis (IR), and scanning electron microscopy analysis (SEM) identified them as a rich source of carbon. Blends were characterized thermally and mechanically showing a direct effect due to the tire nature (thermoset rubber) and concentration. Fracture mechanisms were also identified.